Factors that have influence customer acceptance towards mobile marketing / Ainur Rahmah Mohd Amin and Nurul Natashaina Mohd Mokhtar - Mohd Amin, Ainur Rahmah; Mohd Mokhtar, Nurul Natashaina (Faculty of Business and Management, 2014)
This research is implemented to study about the acceptance towards mobile marketing among Generation Y in Johor Bahru area. The study aimed to identify the major factor that influences the acceptance towards mobile marketing advertisement like entertainment, credibility, informativeness and irritation. The study has been done within the area in Johor.